Co-pyrolysis of sewage sludge and rice husk by TG–FTIR–MS: Pyrolysis behavior, kinetics, and condensable/non-condensable gases characteristics. (November 2020) - Wang, Chengxin; Bi, Haobo; Lin, Qizhao; Jiang, Xuedan; Jiang, Chunlong
Abstract: In this study, pyrolysis behavior, kinetics, and condensable/non-condensable gases characteristics during co-pyrolysis of sewage sludge (SS) and rice husk (RH) were evaluated using Thermogravimetric–Fourier transform infrared spectrometry–Mass spectrometry (TG–FTIR–MS). The mass loss was divided into two stages: the main devolatilization and the continuous slight decomposition of macromolecular substances. The pyrolysis behavior was improved during co-pyrolysis, and the interaction between SS and RH showed synergistic and inhibitive effects. The lowest average activation energy was obtained at 30% RH blending; the Diffusion 3D (Zhrualev–Lesokin–Tempelmen) reaction model can fit the pyrolysis process using the Coats–Redfern method. The functional groups and condensable/non-condensable gases (O-H, C=O, C-O, C-H benzene skeleton, CO, CO2 ) were detected by FTIR, revealing the synergistic effect on the evolution of condensable/non-condensable gases in the promotion of C-O, C=O and CO2 release in blends. The condensable and non-condensable products were detected via MS (including aliphatic and aromatic hydrocarbons, CO2, NOx and SOx). The results showed that CO2 was the main gaseous product and confirmed an enhancement of the CO2 release during co-pyrolysis. The release of both hydrocarbons (C2 H6, C4 H7 +, C4 H8 ) and pollutants (SO, SO2 and toluene) were significantly increased when dealing with pyrolysing the feedstock blend. Highlights: Co-pyrolysis of sewage sludge and rice husk was studied by TG-FTIR-MS. Blending rice husk improved the pyrolysis behavior of blends. The lowest average activation energy was obtained at 30% RH blending. Synergistic effect on the volatiles appeared during co-pyrolysis.